Measuring lateropulsion following stroke in the clinical setting: A feasibility study using Wii technologies - Birnbaum, M.; Brock, K.; Clark, R.; Hill, Keith (WILEY-BLACKWELL, 2015)
Individuals with lateropulsion have difficulty sitting and/or standing upright. Instead, these individuals fall toward their weaker side. People with lateropulsion have trouble maintaining their balance while completing everyday tasks such as showering, dressing and toileting. The current best available assessment for balance requires laboratory equipment, which is not readily available outside university settings. As a result, little is known about the recovery of balance in people with lateropulsion. The aim of this pilot study was to investigate the feasibility of using a Wii Balance Board (WBB) as a measure of balance in people with lateropulsion following stroke. Ten individuals with lateropulsion (mean age 65.6 (13.4 SD) years), between one and twelve weeks post stroke, participated in this study. Participants were assessed on four occasions over a two-week period, performing a number of tasks in sitting and standing on the WBB, in addition to clinical measures. Feasibility was determined by participant retention and compliance with assessment procedures, while redundancy and the proportion of participants who completed each test were examined. Participant retention was 100%. Compliance with assessment procedures was 30%, predominantly due to participant fatigue. Wii Balance Board-derived center of pressure measures appeared to capture useful information about individuals with different levels of lateropulsion severity and displayed change over the study period. The use of WBB technology as a measurement tool with individuals with lateropulsion appears feasible using a reduced number of tasks. Results from this pilot study have informed a larger longitudinal measurement study which is currently underway.